2020
DOI: 10.1038/s41598-020-77322-5
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic tumor growth-inhibitory effect of probiotic Lactobacillus on transgenic mouse model of pancreatic cancer treated with gemcitabine

Abstract: Pancreatic cancer is one of the most lethal and chemo-resistant cancers worldwide. Growing evidence supports the theory that the gut microbiota plays an essential role in modulating the host response to anti-cancer therapy. The present study aimed to explore the effect of probiotics as an adjuvant during chemotherapy for pancreatic cancer. An LSL-KrasG12D/−-Pdx-1-Cre mouse model of pancreatic ductal adenocarcinoma (PDAC) was created to study the effects of using four-week multi-strain probiotics (Lactobacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“… 36 Lactobacillus and Lactobacillus johnsonii , as probiotics in the intestine, are important in maintaining host intestinal homeostasis and regulating host immune response. 37 Lactobacillus has been proved in several studies to have an antitumor effect, 38 , 39 and Lactobacillus johnsonii is also thought to enhance the efficacy of anti–CTLA4. 40 In addition, we found that APS was able to increase the abundance of Faecalibaculum rodentium , which could exert an antitumor effect in a mouse model of colorectal cancer by producing short‐chain fatty acids, while Holdemanella biformis , the bacteria corresponding to Faecalibaculum rodentium in the human body, could also inhibit tumor cell growth in vitro through release of short‐chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Lactobacillus and Lactobacillus johnsonii , as probiotics in the intestine, are important in maintaining host intestinal homeostasis and regulating host immune response. 37 Lactobacillus has been proved in several studies to have an antitumor effect, 38 , 39 and Lactobacillus johnsonii is also thought to enhance the efficacy of anti–CTLA4. 40 In addition, we found that APS was able to increase the abundance of Faecalibaculum rodentium , which could exert an antitumor effect in a mouse model of colorectal cancer by producing short‐chain fatty acids, while Holdemanella biformis , the bacteria corresponding to Faecalibaculum rodentium in the human body, could also inhibit tumor cell growth in vitro through release of short‐chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine treatment is known to cause increased levels of liver enzymes. After combining the treatment with probiotics, a decrease in the level of these enzymes was observed [82].…”
Section: Chemotherapymentioning
confidence: 99%
“…positive lactic acid bacterium located in the human intestine. Adding Lactobacillus paracasei to a mouse model treated with gemcitabine can improve the efficacy of the chemotherapy and increase tolerance [160]. Further research showed that it primarily elevated IFN to transfer the Th2 immune phenotype into the Th1 immune phenotype, subsequently enhancing the antitumor ability [161].…”
Section: The Beneficial Effects Of Bacteria On Pancreatic Cancer Chemotherapymentioning
confidence: 99%